Generation of chimeric minipigs by aggregating 4‐ to 8‐cell‐stage blastomeres from somatic cell nuclear transfer with the tracing of enhanced green fluorescent protein. (11th April 2017) - Ji, Huili; Long, Chuan; Feng, Chong; Shi, Ningning; Jiang, Yingdi; Zeng, Guomin; Li, Xirui; Wu, Jingjing; Lu, Lin; Lu, Shengsheng; Pan, Dengke
Abstract: Background: Blastocyst complementation is an important technique for generating chimeric organs in organ‐deficient pigs, which holds great promise for solving the problem of a shortage of organs for human transplantation procedures. Porcine chimeras have been generated using embryonic germ cells, embryonic stem cells, and induced pluripotent stem cells; however, there are no authentic pluripotent stem cells for pigs. In previous studies, blastomeres from 4‐ to 8‐cell‐stage parthenogenetic embryos were able to generate chimeric fetuses efficiently, but the resulting fetuses did not produce live‐born young. Here, we used early‐stage embryos from somatic cell nuclear transfer (SCNT) to generate chimeric piglets by the aggregation method. Then, the distribution of chimerism in various tissues and organs was observed through the expression of enhanced green fluorescent protein (EGFP). Methods: Initially, we determined whether 4‐ to 8‐ or 8‐ to 16‐cell‐stage embryos were more suitable to generate chimeric piglets. Chimeras were produced by aggregating two EGFP‐tagged Wuzhishan minipig (WZSP) SCNT embryos and two Bama minipig (BMP) SCNT embryos. The chimeric piglets were identified by coat color and microsatellite and swine leukocyte antigen analyses. Moreover, the distribution of chimerism in various tissues and organs of the piglets was evaluated by EGFP expression. Results: We found that more aggregated embryos were produced using 4‐ to 8‐cell‐stage embryos (157/657, 23.9%) than 8‐ to 16‐cell‐stage embryos (100/499, 20.0%). Thus, 4‐ to 8‐cell‐stage embryos were used for the generation of chimeras. The rate of blastocysts development after aggregating WZSP with BMP embryos was 50.6%. Transfer of 391 blastocysts developed from 4‐ to 8‐cell‐stage embryos to five recipients gave rise to 18 piglets, of which two (11.1%) were confirmed to be chimeric by their coat color and microsatellite examination of the skin. One of the chimeric piglets died at 35 days and was subsequently autopsied, whereas the other piglet was maintained for the following observations. The heart and kidneys of the dead piglet showed chimerism, whereas the spinal cord, stomach, pancreas, intestines, muscle, ovary, and brain had no chimerism. Conclusions: To our knowledge, this is the first report of porcine chimeras generated by aggregating 4‐ to 8‐cell‐stage blastomeres from SCNT. We detected chimerism only in the skin, heart, and kidneys. Collectively, these results indicate that aggregation using 4‐ to 8‐cell‐stage SCNT embryos offers a practical approach for producing chimeric minipigs. Furthermore, it also provides a potential platform for generating interspecific chimeras between pigs and non‐human primates for xenotransplantation.